Hoax Related to Covid-19 in Indonesia : A Literacy to Strenghthening Open Government Partnership - Apneta Vionuke Dihandiska; Rino A. Nugroho (Spirit Publik: Jurnal Administrasi Publik, 2021)
At the end of 2019, the world was shocked by the emergence of a new virus, the Covid-19 virus. This virus was first discovered in Wuhan, China in December 2019. According to WHO, Covid-19 is an infectious disease caused by a newly discovered coronavirus. the number of confirmed cases in Indonesia is increasing every day, so in dealing with the Corona outbreak, the role of the government and society is very important to reduce the rate of spread. One sector that needs to be paid attention to by the government and the public in handling this outbreak is the phenomenon of hoax spreading that occurred in the community during this pandemic. Therefore, the government and society must take strategic steps to solve this problem, one of the steps that can be taken is by strengthening the concept of open government partnership that has been run by the Indonesian government since 2011. One of the roles the government can play is to strengthen field data so that the policies taken can be strategic. This can be done by using research related to hoaxes, but in fact there is still little research regarding hoaxes during the pandemic. This research will present the interaction pattern of the infodemic distribution on social media as a basis for government consideration in policy making by taking into account the principles of OGP.